Neuropsychiatric Features of Frontal Lobe Dysfunction in Autopsy-Confirmed Patients with Lewy Bodies and “Pure” Alzheimer’s Disease - Peavy, Guerry M. (2013)
OBJECTIVE: To compare patients with autopsy-confirmed Alzheimer’s disease (AD, #14) and Dementia with Lewy bodies (DLB) on the frequency of behaviors related to frontal systems dysfunction and the association of these behaviors with dementia severity. DESIGN: Cross-sectional survey of longitudinal cohort. SETTING: University Alzheimer’s disease research center. PARTICIPANTS: Volunteer sample of 19 DLB and 38 AD participants with autopsy-confirmed diagnoses, similar in age (DLB: 77.3, AD: 77.5), education (15.2, 14.7), and Mini-Mental State Examination (MMSE) score (20.6, 20.5), with impairment ranging from mild deficits to moderate dementia. MEASUREMENTS: The Frontal Systems Behavior Scale (FrSBe)-Family Rating Form assessing patient apathy, disinhibition, and executive dysfunction by a knowledgeable informant. RESULTS: A two-way analysis of variance with the FrSBe total as the dependent variable revealed a significant MMSE by diagnosis interaction (F(1,53)=9.34, p=.004). Mean FrSBe total for AD patients showed significant impairment across the range of dementia severity, while it was relatively preserved for DLB patients in early stage of disease. The interaction term showed the same pattern for the executive dysfunction (F(1,53)=7.62, p=.008), disinhibition (F(1,53)=4.90, p=.031), and apathy (F(1,53)=9.77, p=.003) subscales. CONCLUSIONS: While frontal behavioral symptoms in AD patients were present regardless of stage of dementia, DLB patients showed significant frontal dysfunction only in later stages. Results suggest that frontal subcortical circuits associated with behaviors assessed by the FrSBe are affected early in AD but not until later stages in DLB. Assessing specific behaviors related to frontal systems, coupled with stage of cognitive decline, may aid in clinical differentiation of AD and DLB.